Adolescents at risk of eating disorders: The mediating role of emotional distress in the relationship between differentiation of self and eating disorders - Peleg, Ora; Boniel-Nissim, Meyran; Tzischinsky, Orna (Frontiers in Psychology, 2023)
Introduction Adolescents may feel dissatisfied with their bodies, which may lead to a risk of eating disorders (EDs) due to several factors, with emotional distress being one of the most important. Evidence suggests that family might be one of the most significant factors that may increase or decrease emotional distress. An important family pattern found to contribute to mental and physical health is the differentiation of self (DoS). The primary purpose of the current study was to map the complex relationships between DoS, emotional distress, and EDs among adolescents. We hypothesized that emotional distress would mediate the relationship between DoS and the risk of EDs among adolescents. Moreover, based on findings indicating a higher risk of EDs among females, we expected sex differences in the research indices and the mediation model. Methods The sample included 194 non-clinical adolescents (mean age 15.15; mean BMI 21.66). Preliminary analyses examined differences between males and females using t-tests. In addition, Pearson correlations were run to assess the association between background variables and the study metrics among males and females. To examine the mediation effect, we ran SEM. Results Due to a sex moderation effect, two mediation models were run (SEM), one for females and one for males. Results indicated that emotional distress partially mediated the relationships between DoS and the risk of EDs. In addition, sex differences were found in the mediated indices, showing that among female adolescents, perfectionism is the only dimension of EDs that was associated with DoS through the mediation of emotional distress. While the relationship between emotional distress and the risk of EDs is well documented. Conclusions It is concluded that high DoS may reduce emotional distress, which may, in turn, decrease the risk of EDs. In addition, the results enable an in-depth understanding of specific risk factors of EDs that characterize each sex.